Innovative Initiatives in Influencing the Success of Solar Energy Implementation in UAE - Abdulwali Alahdal, Mohamed Abdulwahab; Abd Rahman, Md Nizam; Abo Mosali, Najmaddin (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents a research study that investigated the rank of the influence of innovative initiatives’ groups and determined the importance of innovative initiatives to the successful implementation of solar energy adoption in the UAE. The information was gathered via a questionnaire survey and analysed descriptively. The findings of this research work include a ranking analysis of the groups of innovative initiatives, which revealed that administrative innovation ranks first, followed by incremental innovation, technical innovation, radial innovation, process innovation, and finally product innovation in influencing the success of solar implementation in the UAE. For decision on the innovative initiatives on its importance to the successful implementation of solar energy, it was found that technical innovation (RII = .87) appeared as the most important innovation initiative that drive solar energy implementation. This is followed by Incremental innovation (RII =.797), Radical innovation (RII =.773), Process innovation (RII =.764), Administrative innovation (RII =.745), and finally Product innovation (RII =.698). The findings of this study contribute to the body of knowledge on innovative initiatives in successful solar implementation, as well as to the parties involved in solar project implementation.